Comparative analysis of 'La' modified BiFeO3-based perovskite solar cell devices for high conversion efficiency. Issue 1 (1st January 2023) - Raj, Abhishek; Kumar, Manish; Kumar, Arvind; Singh, Kedar; Sharma, Subhash; Singh, Ram C.; Pawar, Manish Singh; Yahya, M.Z.A.; Anshul, Avneesh
Abstract: Among the multiferroic perovskites, BiFeO3 (BFO) shows better efficiency ∼8.1%. In the present work, we have simulated La-doped BFO (BLFO) based on four different perovskite solar cell (PSC) devices with and without electron transport layers (SnO2, ZnO, and TiO2 ) via a computational approach. The present work is a theoretical advancement of previously presented experimental work and provides a proposal for the pathway for higher efficacy in the BLFO as absorber-based PSCs. After the best optimization of the results and found in the proximity of the experimental counterparts, we have further explored the devices concerning the variations in the thickness of absorber and ETLs, band-gap, and electron affinity of the absorber. It is observed that these variations make a high impact on the output parameters (open circuit voltage - VOC, short circuit current density - JSC, fill factor - FF, power conversion efficiency - PCE) of devices. After the comparative investigations of all the devices, it has been concluded that the TiO2 ETL-based device shows better efficiency including the other photovoltaic parameters such as VOC  = 1.23 V, JSC  = 22.24 mA/cm 2, %FF = 86.67, and %PCE = 23.87.